Wood Panel Industries - Ganguly, Dilip K. (Indian Forester, 1970)
The article traces the history of development of wood panel industry in the world. The growth of plywood, fibreboard and particleboard industry in India has been given. The cellulosic raw material requirement of the industries has been considered. The future growth possibilities of these industries have been discussed.